Association Between Gestational Trimester and Hemoglobin Levels among Pregnant Women at Dau Public Health Center, Malang Regency - Reftika Anggraeni; Yeni Avidhatul Husnah (poltekkes kemenkes pontianak, 2026)
Physiological changes during pregnancy, particularly in the second and third trimesters, may affect maternal hemoglobin levels, which play a crucial role in oxygen transport to the fetus. Hemoglobin imbalance during pregnancy may increase the risk of maternal anemia and adverse pregnancy outcomes. This study aimed to analyze hemoglobin levels among second and third trimester pregnant women at Dau Public Health Center, Malang Regency, and to identify factors associated with hemoglobin status. This study employed a descriptive quantitative design using a total sampling technique involving 25 pregnant women, consisting of 13 second trimester and 12 third trimester respondents. Hemoglobin levels were measured using a hematology analyzer, while supporting data were collected using questionnaires related to iron tablet consumption, dietary patterns, antenatal care (ANC) visits, sleep duration, and anemia history. The results showed that the mean hemoglobin level in the second trimester was 11.75 g/dL, while in the third trimester it increased to 12.94 g/dL. Most respondents had normal hemoglobin levels (96%), while only one respondent (4%) demonstrated elevated hemoglobin levels in the third trimester. Routine iron supplementation, regular ANC visits, and adequate nutritional intake were identified as factors associated with normal hemoglobin levels. These findings indicate that most pregnant women at Dau Public Health Center maintained normal hemoglobin status during pregnancy. Regular monitoring of hemoglobin levels and nutritional education remain important to prevent maternal anemia and pregnancy complications.